2008
DOI: 10.1007/s11748-008-0251-x
|View full text |Cite
|
Sign up to set email alerts
|

Current status of coronary artery bypass grafting

Abstract: The number of cases of coronary artery bypass grafting (CABG) reached more than 21 000 in Japan in 2002, and the operative mortality decreased to less than 1%, including emergency operations. The annual number of CABGs in Japan declined 17% after 2003 to 18 000 cases in 2005 owing to unrestricted percutaneous coronary intervention (PCI) with drug-eluting stents. However, CABG is the best treatment for multivessel coronary artery disease based on the comparative data of PCI versus CABG. There have been two tren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 92 publications
0
21
0
Order By: Relevance
“…This is a procedure widely utilized in other countries, however little employed in Brazil even though good results over the short and medium terms have been published [23,24]. Kobayashi [25] concluded, in a population study, that off-pump CABG using only arterial grafts has become the standard procedure in Japan, where 60% of all CABG procedures are performed off-pump and 52% are performed only with arterial grafts giving a mortality rate of less than 1% including with urgent surgeries.…”
Section: -Estimated Probability Free From Re-interventionmentioning
confidence: 99%
“…This is a procedure widely utilized in other countries, however little employed in Brazil even though good results over the short and medium terms have been published [23,24]. Kobayashi [25] concluded, in a population study, that off-pump CABG using only arterial grafts has become the standard procedure in Japan, where 60% of all CABG procedures are performed off-pump and 52% are performed only with arterial grafts giving a mortality rate of less than 1% including with urgent surgeries.…”
Section: -Estimated Probability Free From Re-interventionmentioning
confidence: 99%
“…Notably, the overall proportion of OPCAB increased from 14.5% in 2000 to 21.1% in 2009. This is significantly lower than that reported in European countries who perform multiple arterial grafting in approximately 10-15% of patients, and even more so when compared to rates in Japan (20). We advocate for the use of a greater proportion of arterial grafting for all surgical revascularization, including OPCAB.…”
Section: Overview Of the Opcab Randomized Controlled Trial (Rct) Litementioning
confidence: 64%
“…In Japan, a recent study reported that approximately 60% of CABG were performed using off-pump surgery, and this ratio was even higher in high-risk patients 9) . Recent advances in CABG include the harvesting of skeletonized ITAs.…”
Section: Introductionmentioning
confidence: 99%